(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2025)
This study aims to analyze the capital market’s reaction by examining the differences in stock prices of PT. Sinar Mas Agro Resources and Technology Tbk. before and after the presidential inauguration event on October 20, 2024. The approach used is an event study with a window of 35 days before and after the presidential inauguration. The analytical method employs a Paired Sample t-Test with the assistance of SPSS software. The results indicate a significant value of 0.032 < 0.05, suggesting a market reaction surrounding the presidential inauguration event.